The Use of an Orthopaedic Rating System in Major League Baseball. (September 2014) - McGahan, Patrick J.; Fronek, Jan; Hoenecke, Heinz R.; Keefe, Daniel
Background: Although the majority of Major League Baseball teams use an orthopaedic rating system to evaluate draft picks, little has been published on the topic. Hypothesis: Our goal was to assess the attitudes among Major League Baseball physicians regarding 3 common diagnoses in pitching prospects, through the use of an orthopaedic rating system. Our hypothesis was that the assigned orthopaedic grades would vary among physicians, diagnoses, and operative-versus-nonoperative and recent-versus-past treatment. Study Design: Survey. Level of Evidence: Level 4. Methods: A survey in the form of 12 clinical vignettes was used to query Major League Baseball physicians regarding ulnar collateral ligament (UCL) injuries, type II superior labrum anterior posterior (SLAP) tears, and internal impingement. Respondents graded draft picks using an orthopaedic rating system. The vignettes covered both operative and nonoperative and recent and past treatment (successful return to pitching for 1 year). Results: The orthopaedic grades assigned by respondents were as follows (minimal, moderate, severe risk): past UCL reconstruction (73%, 27%, 0%), recent UCL reconstruction (19%, 77%, 4%), past UCL strain (28%, 60%, 12%), recent UCL strain (0%, 48%, 52%), past SLAP repair (52%, 48%, 0%), recent SLAP repair (4%, 64%, 32%), past SLAP nonoperative (28%, 60%, 12%), recent SLAP nonoperative (0%, 36%, 64%), past internal impingement operative (24%, 68%, 8%), recent internal impingement operative (8%, 32%, 60%), past internal impingement nonoperative (24%, 68%, 8%), and recent internal impingement nonoperative (4%, 48%, 44%). Conclusion: Team physicians are optimistic regarding the outcome of UCL reconstruction. In contrast, UCL strains, type II SLAP lesions, and internal impingement carry a guarded prognosis. For all diagnoses, regardless of treatment, the prognosis improved if a player returned to pitching for 1 full season. Clinical Relevance: This study represents a first step toward developing a standardized orthopaedic rating system that will facilitate more accurate player assessment and clearer communication among physicians.